(3eONd JMdjdjs - (3YHO GdQMef(B, (3Hf YfJQs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2011)
(3EOGQI GdGfJGL(B- (3GdJWhQ GdJGQjNj dEOGQI GdGfJGL(B- (3CKQ JNWjW hJfXje GdYedjGJ GdGfJGLjIYdi GdcaGAI GdGfJGLjI(B- (3CKQ GdQbGHI hGdHQfGeL GdGfJGLj Ydi GdYedjGJ GdEfJGLjI aj JMbjb GdcaGAI GdGfJGLjI(B- (3GdGWGQ GdfXQj ddGfJGLjI hSHd hWQb JMSjfgG(B.s
(3eQGLY U(B.251s
Keywords: (3EOGQI GdGfJGLs; (3GdNOeGJs; (3GdUfGYIs